ALLERGIC RHINITIS: STEROIDS, ANTIHISTAMINES AND MUCOCILIARY CLEARANCE - Salahuddin Ayubi (Journal of University Medical & Dental College)
ABSTRACT Introduction: Allergic rhinitis is very common disease. The efficacy of topical steroid/oral H-1 antihistamine or combined therapy in allergic rhinitis is controversial. Objectives: To see the efficacy of topical steroid/oral H-1 antihistamine/combined therapy on nasal mucociliary clearance in allergic rhinitis. Study design: A comparative study. Setting: ENT Unit, Madina Teaching Hospital, Faisalabad (A tertiary care hospital). Subjects: Random sampling. Thirty six patients in total. Intervention: Saccharine with dye: India ink (Indigocarmine) application on anterior end of inferior turbinate to check mucociliary clearance. Methods: To assess changes in mucociliary clearance time before and after application of topical steroid alone, oral H-1 antihistamine alone and steroid and antihistamine together at fifteen days, one month and two month intervals. Results: Patients were tested for nasal mucociliary clearance. The results showed statistically significant difference (P < 0.05) in group I and III but the results were not significant in group II(P > 0.05). Conclusions: 1. Topical steroids positively modify the nasal mucosal environment in terms of mucociliary clearance. 2. More studies are required in different control conditions to study the longterm effects of steroids and antihistamines on nasal mucosa.